Sex Differences in Response to TNF-Inhibiting Drugs in Patients With Spondyloarthropathies or Inflammatory Bowel Diseases - Laganà, Bruno; Zullo, Angelo; Scribano, Maria Lia; Chimenti, Maria Sole; Migliore, Alberto; Picchianti Diamanti, Andrea; Lorenzetti, Roberto; Scolieri, Palma; Ridola, Lorenzo; Ortona, Elena; Pierdominici, Marina; Bruzzese, Vincenzo (Frontiers in Pharmacology, 2019)
Spondyloarthritis (SpA) and inflammatory bowel diseases (IBD) are chronic inflammatory diseases characterized by an aberrant immune response and inflammation with a key role for TNF in their pathogenesis. Accordingly, TNF-inhibiting therapy (TNFi) has dramatically improved the management of these diseases. However, about 30% of patients discontinue TNFi for lack of response, loss of response, and side effects and/or adverse events. Thus, the possibility to identify in advance those patients who will have a good response to TNFi would be extremely beneficial. The aim of this study was to investigate differences between males and females with either SpA or IBD in response to TNFi molecules, i.e., infliximab (IFX) and adalimumab (ADA), considering the reasons for TNFi withdraw. Data of 594 patients, 349 with IBD (M/F: 194/155) and 245 with SpA (M/F: 123/122), previously unexposed to TNFi, were collected. In the IBD group, the rate of female patients discontinuing ADA was significantly higher than that of male patients (p = 0.03). No difference emerged according to the distribution of reason for discontinuation. Otherwise, a similar discontinuation rate between female and male patients receiving IFX therapy was observed. In the SpA group, the overall discontinuation rate was not different between males and females both for ADA and IFX. However, in patients treated with ADA, males interrupted therapy more frequently than females due to lack of response (p = 0.03). In conclusion, the assessment of sex differences in TNFi response could help physicians personalize the therapeutic approach in a sex-oriented perspective.